Pesticides handling practices among potato growers in Kavrepalanchok, Nepal - Sapkota, Kashi Ram; Sapkota, Sundar; Sapkota, Sanjib; Katuwal, Krishna (Journal of Agriculture and Natural Resources, 2020)
The rate of pesticide application in the agricultural field is surging. Farmers are getting exposed to pesticide hazards from the misuse and unsafe handling of pesticides. The study was conducted among 101 potato growers in Kaverpalanchok district of Nepal in 2018. The objective of the study was to assess the knowledge, status, and pesticide handling practices among potato growers. Around 94% farmers applied pesticides against early and late blight. Only 5% growers treated seed before potato sowing. About 93 and 73% farmers sprayed pesticides 2-10 times/season into the field and spent 2-6 hours/pesticide spray respectively. More than 2/3rd growers did not read the pesticide labels, and nearly 95% growers received information on pesticide applications from agrovet rather than authorized government bodies. Only 13% farmers had received Integrated Pest Management (IPM) training. However, 1/4th of them had practiced IPM techniques. The majority of the growers used masks, rubber boots, and long-sleeved clothes during pesticide handling. Nearly 2/3rd growers threw pesticide containers anywhere in the environment. Concerned authorities should provide IPM training, skill-building programs on pesticide handling and awareness on waiting period and environmental hazards to avoid pesticide risk.